Implementing and managing APPC protected conversations - Bari, Paola (IBM redbooks., 2005)
APPC Protected Conversation is a function provided by the operating system to exploiters running on z/OS. This function improves data integrity in distributed processing environments by enabling participation in the two-phase commit protocol. This IBM Redbooks publication provides system programmers with a solid understanding of the APPC Protected Conversation environment. It describes how to upgrade your environment to support protected conversations, how to configure protected conversation exploiters, how to operate in this environment, and how to manage resources. Sample scenarios illustrate how transactions are executed in a protected conversation environment, and how they fail. Design considerations for avoiding failures are also included, as well as a discussion of tools and utilities for monitoring and tuning your APPC environment. Detailed installation definitions are provided for protected conversation exploiters (IMS, CICS and DB2). Please note that the additional material referenced in the text is not available from IBM.